MANAJEMEN KELAS PENDIDIKAN ANAK USIA DINI (PAUD) DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SISWA DI TAMAN KANAK-KANAK ISLAM TERPADU (TKIT) SABILUL HUDA CIREBON - Asep - Kurniawan (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
The purpose of this study was to find out in depth classroom management of early childhood education in improving student discipline in Islamic fullday Kindergarten Sabilul Huda Cirebon. The research method was qualitative. The instruments were observation, interview, and documentation. Research analysis conducted through collecting data, reducing data, displaying data, and concluding data. The research findings were (1) indoor classroom management in Islamic fullday Kindergarten Sabilul Huda Cirebon supported the implementation of student learning discipline. It was indicated by seating formation, group dynamics, and comfortable classrooms. (2) The outdoor classroom management in Islamic fullday Kindergarten Sabilul Huda Cirebon also supported student learning discipline. This was indicated by the arrangement of facilities and infrastructures, which emphasized safety, comfort and quality. The barriers to indoor classroom management were the lack of learning media and students’ interest in educational activities. The obstacle of outdoor classroom management was the potential for accidents in playing and fighting over toys.